(untitled) (Docentes 2.0 Journal, 2019)
Humanity has gone through different technological revolutions, which have great features have gone from agricultural and artisanal, to industrial, post-industrial and information or knowledge, which is where we do not find today. We are living the deepest technological revolution in the history of mankind.